In-vitro studies of some selected botanicals and baubiofungicide on mycelial growth and conidial germination of Cercospora arachidicola and Cercosporidium personatum - Hossain, MH; Hossain, I (International Journal of Agricultural Research, Innovation and Technology, 2014)
Efforts have been made to assess some plant extracts namely, Lycopersicon esculentum, Tagetus patula, Achras sapota, Azadirachta indica, Datura metel, Cymbopogon citrates, Polyalthia longifolia, Allium sativum and Allium cepa in vitro for the management of leaf spot (tikka) disease of groundnut cultivar Dhaka-1 caused by Cercospora arachidicola and Cercosporidium personatum. Results indicated that all the tested plant extracts and BAUBiofungicide suppressed the growth of mycelium and inhibition of conidial germination of C. arachidicola and C. personatum. Among the treatments, the leaf extracts of L. esculentum showed the most effective followed by leaf extract of D. metel, A. indica and BAU-Biofungicide in case of mycelial growth and conidial germination. Other plant extracts also had inhibitory effects. In case of conidial germination and germination inhibition, the least effective plant extract was C. citrates. Leaf extract of A. sapota was the least effective in case of mycelial growth. DOI: http://dx.doi.org/10.3329/ijarit.v3i2.17842 Int. J. Agril. Res. Innov. & Tech. 3 (2): 36-40, December, 2013